2019
DOI: 10.1186/s12889-019-7318-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of screening on the survival of colorectal cancer in Shanghai, China: a population based study

Abstract: Background Shanghai is one of the earliest cities in developing countries to introduce an organized colorectal screening program for its residents to fight against the rising disease burden of colorectal cancer (CRC). This study aims to investigate the impact of the Shanghai screening program implemented in 2013 on the survival rates of CRC patients. Methods We calculated up to 5-year survival rates for 18,592 CRC patients from a representative district of Shanghai duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 23 publications
3
34
0
Order By: Relevance
“…It has been demonstrated in the US that the mortality of colorectal cancer was greatly reduced by second‐grade prophylaxis, namely, early screening to remove precancerous polyps, early diagnosis, and early surgical resection [ 38 , 39 ]. The government‐supported second‐grade prophylaxis has been carried out for years in several areas in China, resulting in a significant decrease in the incidence and mortality of colorectal cancer in these areas [ 40 , 41 ]. Thus, second‐grade prophylaxis for colorectal cancer should be encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated in the US that the mortality of colorectal cancer was greatly reduced by second‐grade prophylaxis, namely, early screening to remove precancerous polyps, early diagnosis, and early surgical resection [ 38 , 39 ]. The government‐supported second‐grade prophylaxis has been carried out for years in several areas in China, resulting in a significant decrease in the incidence and mortality of colorectal cancer in these areas [ 40 , 41 ]. Thus, second‐grade prophylaxis for colorectal cancer should be encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…CRC continues to impose a high burden on society, as it is constantly claiming many lives worldwide. Thus, prevention and treatment of CRC are of utmost importance, since they can increase survival rates and decrease mortality rates of CRC, as seen in the USA and China [2, 56]. Research has shown that diet may prevent or contribute to CRC through modifying the IM.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed diagnosis related to poor outcomes of CRC, as the previous study found that who had delayed diagnosis were significant with late stage of CRC and breast cancer (Martin et al, 2007;Ermiah et al, 2012;Ortiz-Ortiz et al, 2016) , and with higher mortality of CRC patients (Tørring Tørring et al, 2012). In addition, among participants who had delayed colonoscopy were associated with lower cancer-specific survival (Li et al, 2019), and patient's delay was related to negative result of survival of non-small cell lung cancer patients (Radzikowska et al, 2012). Also, The National Survey of NHS Patients suggested that minimizing diagnostic delays to increase the proportion of early-stage cancers may improve cancer survival in the UK (Allgar and Neal, 2005).…”
Section: Factors Associated With Time Intervals For Diagnosis Of Colomentioning
confidence: 94%